Comprehensive analysis of element and metabolite content between the seeds of Apocynum venetum and Apocynum pictum provides new sights for the salt tolerance in Apocynum - Jiang, Li; Zhao, Yu; Jiang, Zijun; Wu, Yukun; Wen, Bin; Zhang, Siyu; Zhan, Junyi; Su, Nana (Frontiers in Plant Science, 2025)
The genus Apocynum (family Apocynaceae), which includes perennial herbaceous plants, demonstrates remarkable stress tolerance, particularly in saline environments. In this study, we investigated interspecific variations in salt tolerance during the critical germination stage between two predominant Apocynum species, A. venetum and A. pictum. Since seed metabolic processes play a pivotal role in determining germination efficiency and subsequent plant development, seed biochemistry has become an essential parameter for evaluating seed viability and stress resilience. To elucidate the superior salt tolerance mechanism of A. pictum seeds compared to A. venetum seeds, we conducted quantitative analyses of mineral elements using inductively coupled plasma-mass spectrometry (ICP-MS) combined with untargeted metabolomics profiling. The results revealed that most mineral element concentrations were higher in A. pictum seeds than in A. venetum seeds. Furthermore, metabolomic characterization highlighted significant interspecific divergence in both primary and secondary metabolites, especially flavonoids. These multi-omics findings indicate that the coordinated accumulation of stress-protective elements and antioxidant metabolites is a critical determinant of enhanced salt tolerance in A. pictum seeds. Our study provides novel insights into the molecular mechanisms underlying halophytic adaptation in Apocynum species, laying a theoretical foundation for future functional genomics research and genetic engineering strategies aimed at improving crop salt tolerance.